Resource Sustainability, Cooperation Risk Management Capacity and NPO Social Entrepreneurship Activity: A Conceptual Model - Kaoutar Erramy; Said Ahrouch (European Scientific Journal, ESJ, 2021)
Gaining knowledge about social entrepreneurship is important for nonprofit organizations to support their development process. Despite the different studies that treat social entrepreneurship, the role of the Cooperation Risk Management capacity in implementing a social entrepreneurial activity remains an unexplored research field. Scholars have paid particular attention to the capabilities that enable nonprofits to innovate and create social entrepreneurial activities. This paper aims to bridge resources' sustainability and social entrepreneurial activity. For so, social resource-based view theory is mobilized to present a conceptual model that highlights the indirect effect of nonprofit organization's resources sustainability through the mediation of cooperation risk management capacity. This paper sums up with potential implications for future empirical studies.